Beyond formal and informal: Understanding urban informalities from Freetown. (October 2020) - Rigon, Andrea; Walker, Julian; Koroma, Braima
Abstract: Freetown challenges, even more than other cities, entrenched categories of formal and informal. In this paper, the discussion on informality encompasses both the distinction drawn between informal and formal settlements, and between informal and formal economic activities. It is difficult to speak without using these terms given that they are so deeply part of policy discourses in the country by government and development agencies. However, when deployed as an analytical lens, they are demonstrably problematic. Drawing from the findings of a research project, this paper provides insights on what the activities and spaces referred to in policy as "informal" are and what this classification does. It reveals the political use of the term informality, arguing that it is wrong to frame informality as belonging to the poor and challenging the idea that formality and informality are clearly distinct spaces or economic activities in the city. It also demonstrates the fundamental contribution of what policy makers call "informal" to the wellbeing and development of cities, by providing what the state and the "formal" sector are unable to provide: employment and social protection, particularly important for the post-conflict Sierra Leone context. The paper calls for a deep understanding of the contributions of the livelihoods of the residents of informal settlements and a change of criminalisation policies that undermine them. Highlights: challenges entrenched policy discourses on urban in/formality and reveals the political use of the in/formality categorisation provides insights on what the activities and spaces referred to in policy as "informal" are and what this classification does reveals the political use of the in/formality categorisation challenges the idea that informality belongs to the poor, and that formality and informality are clearly distinct demonstrates the fundamental contribution of what policy makers call "informal" to the wellbeing and development of cities shows how the "informal" provides what the state and the "formal" sector are unable to: employment and social protection, particularly important for the post-conflict Sierra Leone context